2021
DOI: 10.3389/fphar.2020.598128
|View full text |Cite
|
Sign up to set email alerts
|

Repurposing Treatment of Wernicke–Korsakoff Syndrome for Th-17 Cell Immune Storm Syndrome and Neurological Symptoms in COVID-19: Thiamine Efficacy and Safety, In-Vitro Evidence and Pharmacokinetic Profile

Abstract: Coronavirus disease identified in 2019 (COVID-19) can be complicated by the Th17 cell-mediated IL-17 proinflammatory response. We tested if thiamine can effectively lower the Th17 response in a clinical study [Proinflammatory state in alcohol use disorder patients termed as disease controls (DC)] and corroborated the results using an in vitro study. We developed an effective dose range and model for key pharmacokinetic measures with the potential of targeting the cytokine storm and neurological symptoms of COV… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 125 publications
0
11
0
2
Order By: Relevance
“…When compared with the hACE2 mouse model, SARS-CoV-2-infected hCD147 mice presented stronger inflammatory responses, including activation of the NF-κB pathway, Th17 cell responses, and activation of proinflammatory cytokine and chemokine signaling pathways, which were all reported to be involved in exudative alveolar pneumonia. 27 , 46 , 47 The difference in the phenotype of hACE2 and hCD147 transgenic mice may attribute to their different expression profile. CD147 is expressed on various types of proinflammatory cells including Th17 cells, neutrophils, NK cells, 48 , 49 where ACE2 is rarely expressed.…”
Section: Discussionmentioning
confidence: 99%
“…When compared with the hACE2 mouse model, SARS-CoV-2-infected hCD147 mice presented stronger inflammatory responses, including activation of the NF-κB pathway, Th17 cell responses, and activation of proinflammatory cytokine and chemokine signaling pathways, which were all reported to be involved in exudative alveolar pneumonia. 27 , 46 , 47 The difference in the phenotype of hACE2 and hCD147 transgenic mice may attribute to their different expression profile. CD147 is expressed on various types of proinflammatory cells including Th17 cells, neutrophils, NK cells, 48 , 49 where ACE2 is rarely expressed.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, because both IL-17 and IL-22 originate in Th17 cells, the dysregulation of the above cytokines could contribute to several proinflammatory diseases ( 206 ). Therefore, applying Th17-inhibiting therapies such as thiamine to reduce the Th17 mediated pro-inflammatory response ( 101 ) may be an effective treatment for decreasing cytokine storms ( 207 ). In one study, 16 patients a proinflammatory state from alcohol use disorder were treated with thiamine, and it significantly reduced IL-17 levels and ameliorated the Th17 responses ( 207 ).…”
Section: Cytokine Secretion Induced By Sars-cov-2 Infectionmentioning
confidence: 99%
“…A very recent study showed a lowering of the Th-17 cell-mediated IL-17 response by thiamine (200 mg per day for three weeks) in patients with elevated proinflammatory cytokines and suggested the use of this vitamin to target the COVID-19 cytokine storm observed in some patients [ 88 ]. We expect that DBT, because of its much higher anti-inflammatory properties compared to thiamine [ 29 ], would be even more efficient.…”
Section: Discussionmentioning
confidence: 99%
“…However, all these effects require rather high concentrations (50–250 µM) of BFT and they may thus not be relevant in vivo. Notwithstanding, thiamine administration in high doses clearly has anti-inflammatory properties in vivo [ 88 ].…”
Section: Properties and Mechanism Of Action Of Benfotiaminementioning
confidence: 99%